Cerebral oxygenation improvement is associated with hemoglobin increase after hemodialysis initiation. Issue 11 (November 2020) - Ito, Kiyonori; Ookawara, Susumu; Ueda, Yuichiro; Miyazawa, Haruhisa; Uchida, Takayuki; Kofuji, Masaya; Hayasaka, Hideyuki; Minato, Saori; Kaneko, Shohei; Mutsuyoshi, Yuko; Yanai, Katsunori; Ishii, Hiroki; et al.
Introduction: Near-infrared spectroscopy has been used to measure the regional oxygen saturation (rSO2 ) of the brain, and decreases in cerebral rSO2 have been reported to lead to cognitive impairment in patients undergoing hemodialysis. However, reports about the association between changes in cerebral oxygenation and clinical parameters at hemodialysis initiation, including hemoglobin level, are lacking. Methods: This study included 33 patients at the hemodialysis initiation phase. Cerebral rSO2 was monitored using an INVOS 5100C. Included patients were assessed twice (at hemodialysis initiation and 42.7 ± 20.8 days after the first measurement), and changes in cerebral rSO2 were compared with changes in clinical parameters. Results: Cerebral rSO2 at the second measurement significantly increased compared with that at hemodialysis initiation (57.2 ± 6.8% vs 54.4 ± 8.8%, p < 0.05). Changes in cerebral rSO2 represented a significant correlation with changes in hemoglobin level, pulse rate, and serum albumin level. Multivariate linear regression analysis was performed using significant factors in simple linear regression analysis. Changes in hemoglobin (standardized coefficient: 0.37) and serum albumin (standardized coefficient: 0.45) levels were identified as independent factors influencing the changes in cerebral rSO2. Conclusion: Cerebral rSO2 was low in the presence of low hemoglobin levels at hemodialysis initiation and improved in response to hemoglobin increase in addition to changes in serum albumin levels. Attention should be paid to changes in hemoglobin levels even at hemodialysis initiation to prevent the deterioration of cerebral oxygenation, and this might contribute to the maintenance of cognitive function in patients undergoing hemodialysis.